EGFR immunoexpression, RAS immunoexpression and their effects on survival in lung adenocarcinoma cases - Gundogdu, Ahmet Gokhan; Onder, Sevgen; Firat, Pinar; Dogan, Riza (Journal of Thoracic Disease, 2014)
Background: The impacts of epidermal growth factor receptor (EGFR) immunoexpression and RAS immunoexpression on the survival and prognosis of lung adenocarcinoma patients are debated in the literature. Methods: Twenty-six patients, who underwent pulmonary resections between 2002 and 2007 in our clinic, and whose pathologic examinations yielded adenocarcinoma, were included in the study. EGFR and RAS expression levels were examined by immunohistochemical methods. The results were compared with the survival, stage of the disease, nodal involvement, lymphovascular invasion, and pleural invasion. Nonparametric bivariate analyses were used for statistical analyses. Results: A significant link between EGFR immunoexpression and survival has been identified while RAS immunoexpression and survival have been proven to be irrelevant. Neither EGFR, nor RAS has displayed a significant link with the stage of the disease, nodal involvement, lymphovascular invasion, or pleural invasion. Conclusions: Positive EGFR immunoexpression affects survival negatively, while RAS immunoexpression has no effect on survival in lung adenocarcinoma patients.